8(x+13)=12(x-8)

Simple and best practice solution for 8(x+13)=12(x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x+13)=12(x-8) equation:


Simplifying
8(x + 13) = 12(x + -8)

Reorder the terms:
8(13 + x) = 12(x + -8)
(13 * 8 + x * 8) = 12(x + -8)
(104 + 8x) = 12(x + -8)

Reorder the terms:
104 + 8x = 12(-8 + x)
104 + 8x = (-8 * 12 + x * 12)
104 + 8x = (-96 + 12x)

Solving
104 + 8x = -96 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
104 + 8x + -12x = -96 + 12x + -12x

Combine like terms: 8x + -12x = -4x
104 + -4x = -96 + 12x + -12x

Combine like terms: 12x + -12x = 0
104 + -4x = -96 + 0
104 + -4x = -96

Add '-104' to each side of the equation.
104 + -104 + -4x = -96 + -104

Combine like terms: 104 + -104 = 0
0 + -4x = -96 + -104
-4x = -96 + -104

Combine like terms: -96 + -104 = -200
-4x = -200

Divide each side by '-4'.
x = 50

Simplifying
x = 50

See similar equations:

| -4-7=-8+x | | -5x-10-14=15+1 | | x=18d | | y-14=8 | | 6x-8=9x+25 | | x^3-2x^2+2x=0 | | (19b-1)-9(2b+3)=-4 | | f(x)=3(9)-7 | | -3(7p+3)-2(2-20p)=3(9+6p) | | y=5/9x+40/9 | | -1.7-5.56(x+5.54)=6.95 | | x*2=-4 | | 3(5x+9)-3(x-7)=11(x-2)+7 | | 13x-11=9x+5 | | 24y-15=9y | | 8-5x=10+3x | | 3w-14=37 | | 7x+5=4x+32 | | 14=x+21 | | 2(4x+5)-7= | | 11=x+21 | | -4x-7=33 | | 20+12z=13z | | 7x+8=85 | | -6x-7=-1 | | (2/3a^2+b^2)^3+(2/3a^2-b^2)^3-4/3a^2(2/3a^2+b^2)(2/3a^2-b^2)-10/3a^2b^4 | | 41y=40y-30 | | 6-7x=-71 | | 4(x-2)+1=5(x+1)-3x | | -4k+2(5k-6)=-33k-39 | | -76=6x+6x-4 | | 100x-(55x+40)=15 |

Equations solver categories